Role of Artificial Intelligence in Intra-Sectoral Wage Inequality in an Open Economy: A Finite Change Approach - Shreya Roy; Sugata Marjit; Bibek Ray Chaudhuri (Center for Economic Studies and ifo Institute (CESifo), 2022)
Artificial Intelligence (AI) has the potential to significantly impact the income of individuals. Cross-country data shows that introduction of AI is inequality enhancing in developing and less developed countries. In this paper, we attempt to understand the reason for increase in wage inequality across labourers due to introduction of AI, in a finite change General Equilibrium (GE) set up which allows for emergence of a new activity. AI-induced technological shock is introduced in the non-traded sector of an open economy with heterogeneous skills. We show how the advent of AI (which was initially non-existent) in the non-traded sector separates the skills of the once homogenous workers, thus, creating an intra-sectoral wage gap. What proportion of the low-skilled workers can move to the higher wage paying sector depends on an adaptability factor that acts as an eligibility criterion in fragmenting the erstwhile homogenous labourers and also works towards rising intra-group wage gap.
Keywords: O33; J31; D50; 330; artificial intelligence; finite change; sectoral wage gap